Nepal at the Crossroads: Setting the Stage for Improved Social Health Protection - MoHP-GTZ (Deutsche Gesellschaft fur Technische Zusammenarbelt (GTZ) GmbH, 2012)
The Ministry of Health and Population (MoHP) of Nepal is seeking to expand social health protection (SHP) by improving health care financing and searching for appropriate ways to do this. To this end, MoHP and GTZ have started jointly to assess the current social health protection status and to outline various policy options, suiting the Nepalese context. This led to a dedicated effort in May 2010 during which representatives of MoHP, GTZ staff, a representative from the Providing for Health (P4H) Initiative as well as an international and a national consultant have together met various stakeholders, visited the districts, their health authorities and some of their health care facilities. This report reflects the findings of this joint effort and is meant to more explicitly and in-depth discuss policy options for health financing improvement, set preliminary priorities to form a basis for further engagement and explore the preferred option or options. The report discusses (i) the current policy environment and its implications for changing current health financing mechanisms, (ii) the available fiscal space to expand revenues for the sector and by freeing up resources by enhancing efficiency in administration and health services delivery, (iii) the health financing and social health protection (SHP) context of Nepal, (iv) the preconditions for introducing new financial arrangement, (v) the policy options for new health financing arrangements, and it ends with some recommendations and suggestions for next steps.